Pengembangan Model Denitrification Decomposition (DNDC) Untuk Pendugaan Emisi Gas Metana (CH4) Dari Lahan Padi Sawah - Nisha, Fitriani Nurhayatin; Arif, Chusnul (Departemen Teknik Sipil dan Lingkungan IPB, 2019)
Cultivated paddy fields that applied in Indonesia currently produces high emissions of greenhouse gases (GHG), particularly methane gas (CH4). This research aimed to analyze CH4 gas emission in various water management, and to develop DNDC model in predicting CH4 gas emission. This research was conducted from January to May 2018, located at field laboratory of Departement of Civil and Environmental Engineering. The research was conducted by three water regimes i.e., continuously flooded (RT) for conventional rice farming, wet regime (RB), and dry regime (RK) for system of rice intensification (SRI). The highest total methane (CH4) flux was 48.74 kg/ha on RT, on RB was 3.59 kg/ha and on RK -5.40 kg/ha. DNDC model needed data inputs of climate, soil physics, vegetation and anthropogenic activities. The result of the DNDC model showed that the highest total CH4 flux was 44.44 kg/ha on RT, on RB was 17.88 kg/ha and on RK was 0.02 kg/ha. The result, of total actual of CH4 gas flux was compared with DNDC model and got the coefficient of determination (R2) values 0.93, so the model could be used to predict total CH4 gas emission.Keywords: DNDC, methane gas, paddy field, water regime.